GAMBARAN PERILAKU PASIEN TB PARU TERHADAP UPAYA PENCEGAHAN PENYEBARAN PENYAKIT TB PARU PADA PASIEN YANG BEROBAT DI POLI PARU RSUD ARIFIN ACHMAD PROVINSI RIAU - Iklima Asiah; Suyanto "; Sri Melati Munir (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Tuberculosis (TB) pulmonary is a contagious infectious disease caused by Mycobacteriumtuberculosis that attacks the lungs. The prevalence of pulmonary TB disease can beprevented when patients have pulmonary tuberculosis good behavior for prevention of TBlung disease spread.The behavior consist of three is knowledge, attitude and practice. Thepurpose of this study is knowing description of behavior pulmonary TB patient to preventthe spread of pulmonary TB disease in patient seeking treatment in lung poly ArifinAchmad hospital province of Riau.This study was conducted in Februari-Maret 2014. Thesubject of this study were 115 pulmonary TB patient which inclusion criterias. This studyused questionnaires as instruments. The result of this study showed that rspondents had agood knowledge of as many 50 people (43,5%), good attitudes as many as 81 people(70,4%) and good practice as many as 53 people (46,1%).Key words : Tuberculosis (TB) pulmonary, knowledge, attitude dan practice prevention ofpulmonary TB disease, pulmonary TB patient